Perencanaan Investasi Pembangunan Perumahan Di Desa Gedongan Kecamatan Colomadu Kabupaten Karanganyar - Pratama, Rafikal; , Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
Housing in Solo grows very rapidly, particularly in Gedongan village, Colomadu, Karanganyar. This location is very fast in terms of housing projects development because of its location that close to the center of Solo city. In housing investment planning projects, generally require substantial funds, because it is necessary to do a feasibility study to avoid unprofitable investment. Where the distribution of the questionnaires are used to determine how the demand of houses in Gedongan village and conducted feasibility studies in terms of economic aspects comprising the calculation of PP, ROI, NPV, IRR, BCR and IP, as well as BEP to understand when the break-even investment obtained. After the analysis is done, we concluded that, planned 16 houses in the village Gedongan with total area of 2160 m2, in the economic analysis that includes PP with annual cash flow with a fixed number of values obtained 22 months and 3 days, while the annual cash flow by the number that not fixed obtained the value of 20 months and 3 days, the ROI is worth 4.53% per month = 54.32% per year, ROI after tax per month is worth 4.07% per month = 48.89% per year, the NPV scored positive to value of RP 547.672.714,24; IRR is worth 19.82%> interest rate of 10%, BCR worth 1,069 > 1, and IP worth 1.069 > 1, for BEP is reached when sold at 13 unit of houses. Thus the housing developments planning in Gedongan village, Colomadu, Karanganyar is worth to be implemented.